Analysis Of The Application Of Psak 109 Regarding Zakat, Infaq, And Alms At Lazis Nahdlatul Ulama - Anita Dwi Utami (LPPM Universitas Sebelas April, 2023)
Allah provision regarding the use of property that must be followed by humans is the provision regarding zakat. The government realizes that if zakat management is carried out properly, transparently and responsibly, many social and economic problems in society can be solved. Reporting on Zakat Infaq and Alms Funds is regulated in the Pernyataan Standar Akuntansi Keuangan (PSAK) 109 concerning Accounting for Zakat, Infaq and Alms. The results of previous research regarding PSAK 109, there are still many Amil Zakat Institutions that have not implemented PSAK 109, so the purpose of this study is to examine the extent to which the implementation of zakat, infaq, and alms financial reporting standards regulated by PSAK 109 in Amil Zakat Institutions. The method used in this study is descriptive analysis with the research object being the Amil Zakat Infaq and Sadaqah Nahdlatul Ulama Institute (LAZISNU). The results of the study show that LAZIS Nahdlatul Ulama for recognition, measurement, disclosure and presentation is in accordance with PSAK 109 concerning Accounting for Zakat, Infaq and Alms.